Resident Networks and Corporate Connections: Evidence from World War II Internment Camps - COHEN, LAUREN; GURUN, UMIT G.; MALLOY, CHRISTOPHER (Journal of Finance, 2017)
ABSTRACT Using customs and port authority data, we show that firms are significantly more likely to trade with countries that have a large resident population near their firm headquarters, and that these connected trades are their most valuable international trades. Using the formation of World War II Japanese internment camps to isolate exogenous shocks to local ethnic populations, we identify a causal link between local networks and firm trade. Firms are also more likely to acquire target firms, and report increased segment sales, in connected countries. Our results point to a surprisingly large role of immigrants as economic conduits for firms.